DESIGN OF BAMBOO STICK POLISHING MACHINE WITH 12 TON/MONTH CAPACITY - Kurniawan, Kurniawan; Setiawan, Heri; Sujana, Dede; Fauzan Hardiansyah , Ilham (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Local bamboo stick products are still unable to compete with imported bamboo stick on the market due to the high cost of production. The production of bamboo stick has several stages, including cutting bamboo blades, removing bamboo skin, forming square blades, forming circle profiles, cutting lengths, smoothing, sharpening, and drying. Currently, the refining process at the Booboo Walini Workshop has an uneven level of uniformity. In the design process of this polishing machine, the VDI 2222 design methodology is used. The way this machine works is that the bamboo stick will be inserted into a cylindrical finned reservoir and then rotated within + 1 hour. The skewers will contact each other and rub against each other which can smooth the surface of the bamboo stick from the fibers. In determining the optimal geometry and number of fins in the reservoir, simulations were carried out using Altair EDEM software with a Discrete Element Method (DEM) approach and considering the optimal number of contacts during the polishing process. This machine is driven by an electric motor with a power of 1.1 kW and an output rotation of 16 rpm. This polishing machine has a production capacity of 461.5 kg daily with a storage dimension of ∅597.3 × 680 mm.